(3QSGdI aj abg GdRjOjIs - (3RjO Hf Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH , CHh GdMSjf GdYdhqj GdgGTej GdbQTj , hjbGd dg (B((3RjO GdTgjO(B) (3, (B122 (3g` s ((3MSjf Hf eMSf s)
(3ChdgG (B:s
(3jHOC HHGH eJi jLH Ydi Cgd GdYOd bJGd GdaFI GdHGZjI s
(3BNQgG (B:s
(3jfJgi HcJGH GdfcGM , HGH aVd GdfcGM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQJH GdGHLOi s
Keywords: (3abg GdePGgH GdCNQis